Influence of the n-paraffin molecule hydrocarbon chain length in the composition of diesel fuel on the effectiveness of the depressant - Morozova Ya. P. Yana Pavlovna (Химия и химическая технология на иностранном языке (английский), 2022)
Заглавие с титульного экрана